THE SYSTEM OF BUYING AND SELLING ARISAN MONEY IN ANTHROPOLOGY REVIEW OF ISLAMIC LAW (Case Study In Toteker Hamlet, West Banuaju Village, Batang-Batang, Sumenep) - Fatah, Hairil; Nashirudin, Muh; M Usman (Universitas Muhammadiyah Surabaya, 2023)
The sale and purchase of arisan money in Toteker Hamlet, West Banuaju Village, Batang-Batang District, Sumenep is a practice that has been carried out for generations, not only by members of the arisan from among the farmers, but also by members of community leaders, and the parties involved become the power it is interesting to reveal the reasons and factors behind it, as well as the unclear status of Islamic law. This study aims to analyze the system of buying and selling arisan money in an anthropology review of Islamic law, revealing the identity of the parties involved, the underlying factors, and the reasons for carrying out the practice of buying and selling. This research method uses field qualitative methods with data collection procedures through observation, interviews, and documentation. The results showed that the system of buying and selling arisan money is an act that is forbidden because there is an additional advantage from buying and selling money with the same type of money, this is done under forced circumstances, and there is hilah done by one of the community leaders.Keywords: Anthropology, Buying and Selling, Arisan